2015
DOI: 10.1088/0031-9155/60/5/2103
|View full text |Cite
|
Sign up to set email alerts
|

Field size dependent mapping of medical linear accelerator radiation leakage

Abstract: The purpose of this study was to investigate the suitability of a graphics library based model for the assessment of linear accelerator radiation leakage. Transmission through the shielding elements was evaluated using the build-up factor corrected exponential attenuation law and the contribution from the electron guide was estimated using the approximation of a linear isotropic radioactive source. Model parameters were estimated by a fitting series of thermoluminescent dosimeter leakage measurements, achieved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…Discrepancies between calculations and measurements were found to be about 10%. In a similar manner, VũBezin et al [78] found discrepancies between leakage measurements and calculations to be below 7% for points within 100 cm of the central beam axis.…”
Section: Estimation Of the Dose At The Point Or Volume Of Interestmentioning
confidence: 65%
See 1 more Smart Citation
“…Discrepancies between calculations and measurements were found to be about 10%. In a similar manner, VũBezin et al [78] found discrepancies between leakage measurements and calculations to be below 7% for points within 100 cm of the central beam axis.…”
Section: Estimation Of the Dose At The Point Or Volume Of Interestmentioning
confidence: 65%
“…This has led medical physicists to develop in-house algorithms for estimating out-of-field doses. Three main categories of out-of-field dose algorithms exist: measurement-based algorithms [6, 14-16, 72, 76, 77], multi-source algorithms [17,78] and Monte Carlo (MC) algorithms [44,79,80].…”
Section: Estimation Of the Dose At The Point Or Volume Of Interestmentioning
confidence: 99%
“…Analytical models, on the other hand, are comparatively simple, fast, and free of statistical fluctuations. There is also promising evidence suggesting they can be dosimetrically accurate in the out‐of‐field region . Further, a recently published analytical model is readily generalizable to different treatment machines and irradiation conditions without the need for proprietary information due to its physics‐based framework .…”
Section: Introductionmentioning
confidence: 99%
“…Out-of-field dose is an unintended consequence of radiation therapy that may increase the risk of late effects such as myocardial damage [1][2][3][4][5] and secondary cancers. [6][7][8] Out-of-field dose consists of three main components: head leakage, 9,10 internal scatter, 11 and collimator scatter. Unlike internal scatter which is an unavoidable radiation dose, head leakage can and should be minimized.…”
Section: Introductionmentioning
confidence: 99%